TAHFIDZ AL-QUR’AN DI PONDOK PESANTREN: (Pengertian, Metode, dan Keutamaannya) - Nazopah, Nada (STIT Al-Aziziyah, 2024)
This paper discusses the meaning, methods, and virtues of Qur'an memorization in Islamic boarding schools. This paper will first include the definition of Qur'anic memorization, its methods, and its virtues. The second section examines Islamic boarding schools and their virtues. The third section discusses Qur'an memorization in Islamic boarding schools and its virtues. The tahfidz program aims to produce hafidz (memorizers) who can memorize all 30 juz of the Qur'an properly and correctly according to the rules in the Qur'an, the implementation of which will be maximized if carried out in boarding schools. This paper is a literature study by collecting data from various literature and information from available sources such as books, journals, reports, and other documents